5 lucky scientists DOING US PROUD: They are first to join international research institutions CERN and IIASA - New Straits Times, Awaina Arbee (2012)
FIVE young scientists will go down in Malaysian history as the first ones to do research projects with two prestigious institutions - International Institute for Applied Systems Analysis (IIASA) and Organisation of European Nuclear Research (CERN). Malaysian Science Academy president Tan Sri Ahmad Tajuddin Ali said yesterday the five were selected by the two institutions for the research projects.